Solid Waste Generation and Characterization in a State University - Pangandaman, Merhanna; Acabal, Josua Meko; Anino , Cesar; Apat, Gerald (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the solid waste generation and characterization at Mindanao State University (MSU) - Main Campus in Marawi City, addressing the critical issues of unsustainable waste management practices. Despite the recent establishment of waste management facilities in Marawi City, including a Central Material Recovery Facility (CMRF) and a Category 4 Sanitary Landfill (SLF), the campus and much of the city need help with effective waste disposal. This has led to environmental challenges such as clogged drainage systems, open dumping, and air pollution from waste burning. The study fills an essential gap in solid waste generation and characterization data, which is crucial for effective solid waste management (SWM) planning as mandated by the Ecological Solid Waste Management Act of 2000 (RA 9003). Using a descriptive-comparative research design, the study surveyed 216 units, including residential buildings, rental properties, commercial establishments, and university facilities. The findings reveal that the MSU-Main Campus generates 9438.011 kg of waste daily, with a per capita waste generation rate of 0.9371 kg/day— significantly higher than the national average. Residential buildings are the primary waste generators, contributing nearly half of the total waste, followed by lodgings. Waste characterization reveals a substantial proportion of non-biodegradable waste (38.29%), with biodegradable waste accounting for 35.46% of the total. These findings highlight the urgent need for systematic waste management strategies, particularly focusing on waste segregation, recycling, and waste reduction to mitigate the environmental impact on campus. The study provides a comprehensive data foundation for developing a solid waste management plan and underscores the role of academic institutions in leading sustainable practices.